Electrical Stun Gun and Modern Implantable Cardiac Stimulators: Update for a New Stun Gun Model. Issue 3 (March 2021) - Mattei, Eugenio; Censi, Federica; Calcagnini, Giovanni
Abstract : Abstract: In 2017, the Italian National Institute of Health conducted a study to evaluate the potential risks of Conducted Electrical Weapons (CEW, AKA "stun guns") for users bearing a pacemaker (PM) or an implantable cardioverter defibrillator (ICD). The study addressed two specific models of stun guns: the TASER model X2 and AXON model X26P. In 2019, the same experimental protocol and testing procedure was adopted to evaluate the risk for another model of stun gun, the MAGEN model 5 (MAGEN, Israel). The MAGEN 5 differs from the previous stun guns tested in terms of peak voltage generated, duration of the shock, and trigger modality for repeated shocks. This note is an update of the previous study results, including the measurements on the MAGEN 5 stun gun. Despite the differences between the stun gun models, the effects on the PM/ICD behavior were the same as previously observed for the TASER stun guns.